Stature estimation: evaluating regression equations for different population groups in South Africa - Arendse, Liesl Margo (Department of Human Biology, 2019)
Stature estimations from regression formulae are used by forensic anthropologists in constructing a biological profile from unidentified human remains. Regression formulae are used to calculate total skeletal height or living stature when incomplete, fragmentary or burned human remains are recovered. This study aimed to evaluate the reliability of the total skeletal height regression formulae from (1) Lundy and Feldesman (1987), and (2) Dayal et al. (2008) when compared to total skeletal height from the full anatomical method (Fully’s method), in a contemporary South African population. The use of these regression formulae to estimate total skeletal height of South Africans of Mixed Ancestry was investigated as no population-specific standards exist for this group. Additionally, the reliability of the generic femur/stature ratio (Feldesman et al., 1990) to estimate living stature for all three population groups was investigated. Measurements were taken from 229 individuals comprising of South Africans of Mixed Ancestry, African Descent and European Descent from South African skeletal collections. ANOVA’s and paired t-tests were used to determined if there was a significant difference (p<0.05) between (1) estimated total skeletal height from regression formulae and that from Fully’s method, and (2) the estimated living stature from the femur/stature ratio and a calculated living stature from Fully’s total skeletal height with soft tissue and age correction factors. No significant difference (p>0.05) was found between South Africans of African Descent and Mixed Ancestry’s calculated total skeletal height, but both were significantly different (p<0.000) to individuals of European Descent. Results indicate that the Lundy and Feldesman (1987) regression formulae should be re-assessed for contemporary South Africans of African Descent and results from the Dayal et al. (2008) regression formulae indicate that the formulae are still relevant for contemporary South Africans of European Descent. Additionally, new regression formulae should be developed to enable forensic or physical anthropologists to estimate total skeletal height of Mixed Ancestry individuals. The femur/stature ratio’s living stature were significantly different (p<0.000) from the calculated living stature, and generally overestimated it for maximum femur lengths greater than 50cm.